The Improvement of Employee Performance by Public Service Management of Hospital in Bukittinggi City - Bila, Aziza; Assyahri, Wahib; Oktaviane, Diga Putri (Faculty of Social Science, Universitas Negeri Padang, 2023)
Employee performance is a key factor in organisations and is still a serious concern today, as it is directly related to the success of the organisation. Employee performance must be responsible and professional, which is achieved by carrying out tasks seriously, providing services quickly, easily and cost-effectively and treating every customer fairly. One factor that is still little known but has a very strong influence on performance is Public Service Management (PSM). PSM is assumed to be a factor influencing performance because this theory states that employee behaviour is influenced by the socio-historical context, motivation and characteristics of the employees themselves and is not solely the result of job requirements. The behavioural factor of job satisfaction is assumed to be the bridge between PSM and employee performance. In general, this study aims to prove the existence of linkages between the dimensions described above. Specifically, this study determines the direct effect of PSM on employee performance and the indirect effect of the two dimensions through the behavioural dimensions of innovation and job satisfaction. This research was conducted using a quantitative approach for one year. The research data were collected through a questionnaire that had been validated and reliable beforehand. Data collection was carried out on research samples drawn by total sampling technique. The collected data will be analysed using SEM. The results of the study state that there is an indirect and indirect effect of PSM variables on performance